Teknologi Web sebagai Media Pelestarian Budaya Batak Toba Secara Khusus Marga Samosir Se-JABODETABEK - Ridha Sefina Samosir; Elsa Shahnaz Aprilia (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
Batak Toba is one of the largest tribes in Indonesia. Batak Toba is known by many family names or clans, one of which is the Samosir. One of the characteristics of Batak Toba is nomaden and form a community in overseas places so that they remain connected to one another. This community can represent clans, regional origins, religions, and others like Samosir community in JABODETABEK area. This community consists of a number of members live in JABODETABEK, including Bogor, East Jakarta, South Jakarta, West Bekasi, East Bekasi, Depok, South Tangerang, and others. The existence of this very large membership requires effective management of membership data to make it easier for the coordinator to operate their activities, formulate a strategic plan, and helping decisions making. Specifically for Batak Toba tribe, there are two special supporting data. This special data is not shared by other ethnic communities. This special data is the serial number in the family tree and the ompu name. Specific data will affect the procedure for summoning and the position of a person in every traditional culture activity, both joy and sorrow. Media proposed in this study is the website. Based on data collected through the website, it shows that out of 600 members of the Samosir clan throughout JABODETABEK, around 450 data or around 75% have been identified during the data collection process in two months.